Effectiveness of a standardised patient simulation programme in undergraduate nursing students 6 months after implementation: A quasi‐experimental study - María José Cabañero‐Martínez; Silvia Escribano; María Sánchez‐Marco; Rocío Juliá‐Sanchis (Wiley, 2023)
Abstract Aims The objectives were to evaluate the effectiveness of a standardised patient simulation programme and to analyse to what extent the students transferred the skills covered in the simulation to clinical practice 6 months after the intervention. Design A quasi‐experimental study was carried out, with measurements taken pre‐, post‐ and 6 months after the implementation of a standardised patient simulation programme in a single group. Methods Eligible to participate were all final year nursing undergraduates during the 2020-2021 academic year. In total, 41 undergraduate nursing students took part in all stages of the study. It was measured attitude towards communication, self‐efficacy, communication skills and resilience. The degree to which communication skills were used in the real setting was also assessed. Results The students' scores for self‐efficacy and perceived communication skills improved and were maintained after six months. Regarding to resilience, improvement was even evident six months following the intervention. In terms of the transfer to clinical practice, the students were making moderate to high use of the communication skills learned in the simulation.